2003
DOI: 10.1002/ijc.11185
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathway for aloe‐emodin‐induced apoptosis in human H460 lung nonsmall carcinoma cell

Abstract: Aloe-emodin (1,8-dihydroxy-3-(hydroxymethyl)-anthraquinone) is an active component from the root and rhizome of Rheum palmatum that has been reported to exhibit antitumor effects through an unknown mechanism. Our study investigated the mechanisms of aloe-emodin-induced cell death in the human lung nonsmall cell carcinoma cell line H460. Aloe-emodin (40 M)-induced apoptosis of H460 cells involves modulation of cAMP-dependent protein kinase, protein kinase C, Bcl-2, caspase-3 and p38 protein expression. Rheum pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Emodin at 50 mg/l and 100 mg/l reduced p-p38 levels by 40% and 73%, respectively. This finding is consistent with other in-vitro studies using human umbilical vein endothelial cells (Kwak et al, 2006), human lung non-small cell carcinoma cells (Yeh et al, 2003), and retina ganglion cells (Lin et al, 2007) in which the pharmacological effect of emodin was mediated via inhibition of p38. Our previous study also demonstrated that emodin normalizes IL-1β induced mesangial cell p38 over-activation (Wang et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Emodin at 50 mg/l and 100 mg/l reduced p-p38 levels by 40% and 73%, respectively. This finding is consistent with other in-vitro studies using human umbilical vein endothelial cells (Kwak et al, 2006), human lung non-small cell carcinoma cells (Yeh et al, 2003), and retina ganglion cells (Lin et al, 2007) in which the pharmacological effect of emodin was mediated via inhibition of p38. Our previous study also demonstrated that emodin normalizes IL-1β induced mesangial cell p38 over-activation (Wang et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…While phylloquinone has no apoptosis-inducing activity in animal cells, such activity has been found for both the related menaquinone (vitamin K2) and several anthraquinones (Miyazawa et al, 2001;Lin et al, 2003;Yeh al., 2003). The synthetic, water-soluble menadione (vitamin K3) is also a potent inducer of PCD in tobacco protoplasts (Sun et al, 1999), and menadione bisulphite induces rapid and extensive leaf necrosis when sprayed onto Arabidopsis plants at 1 to 3 mM concentration (P. Brodersen and F.G. Malinovsky, unpublished data).…”
Section: Discussion Nahg Substrates Different From Sa May Be Involvedmentioning
confidence: 99%
“…Downregulated Bcl-2 along with unaffected Bax was found in human H460 non-small-cell lung cancer cell lines. 2 Upregulation of the Bax/Bcl-2 ratio was reported in human neuroblastoma cell lines SJ-N-KP 23 and human lung squamous carcinoma cell line CH27. 22 Emodin decreased Mcl-1, but did not significantly affect the expressions of Bcl-2 and Bax proteins in myeloma cells, such as U266, IM-9, KMS-12-PE, RPMI8226, 1 and HL-60, 24 have also been reported.…”
Section: Mechanisms Of Emodin For Leukemiamentioning
confidence: 99%
“…(Figure 1). Emodin shows a wide variety of pharmacological activities such as anticancer, [1][2][3][4] antifibrosis, [5][6][7] antirestenosis, 8,9 and antimicrobial activities. 10 However, emodin is poorly soluble in water, which limits its applications in vivo.…”
Section: Introductionmentioning
confidence: 99%